Capacity of healthcare facilities in the implementation of Direct Observed Treatment strategy for tuberculosis in Arumeru and Karatu districts, Tanzania - Mfinanga, GS; Ngadaya, E; Kimaro, G; Mtandu, R; Lema, LA; Basra, D; Lwila, F; Egwaga, S; Kitau, AY (Tanzania Journal of Health Research, 2008)
Directly Observed Treatment Short course strategy (DOTS) has proved to have potential improvement in tuberculosis (TB) control in Tanzania. The objective of this cross sectional study was to assess the capacity of health facilities in implementing DOTS, in Arumeru and Karatu districts, Tanzania. Information sought included the capacity to offer TBservice and availability of qualifi ed staff and equipment for TB diagnosis. Information on availability and utilization of TB registers and treatment outcome for the year 2004 were also collected. A total of 111 health facilities were surveyed, 86 (77.5%) in Arumeru and 25 (22.5%) in Karatu. Only 23.4% (26/111) facilities were offering TB treatment services inthe two districts. Majority 17/26 (65.38%) of them were government owned. Thirty eight (44.7%) facilities were offering TB laboratory services. All facilities with TB services (TB laboratory investigation and treatment) had TB registers. Seventy two (85.0%) of health facilities which do not provide any TB services had qualifi ed clinical offi cers and at leasta microscopy. Of the 339 cases notifi ed in Arumeru in 2004, 187 (60.7%) had treatment outcome available, 124 (66.3%) were cured and 55 (29.4%) completed treatment. In Karatu 638 cases were notifi ed in 2004, 305 (47.8%) had treatment outcome available, 68 (22.3%) cured and 165 (54.1%) completed treatment. In conclusion, the overall capacity for implementing DOTS among the facilities surveyed is found only in about 20% and 30% for clinical and laboratory components of DOTS, respectively. The capacity to provide TB diagnosis and treatment in Karatu district was relatively lower than Arumeru. It is important that capacity of the facilities is strengthened concurrently with the planned introduction of community- based DOTS in Tanzania. Keywords: tuberculosis, control, community, DOTS strategy, Tanzania Tanzania Journal of Health Research Vol. 10 (2) 2008: pp. 95-98